Analysis on the buckling performance of embedded co-cured composite sandwich plates under uniaxial compression condition. (1st November 2022) - Wang, Shaoqing; Guo, Anfu; Zheng, Changsheng; Liang, Sen
Abstract: The research aims at exploring the buckling behavior of embedded co-cured composite sandwich structure (ECCSS) under static load. In accordance with the research objective, an analytical model, which is based on the interlayer stress continuous theory to formulate governing differential equations for predicting the critical buckling loads of ECCSS, has been established. The theoretical solution that satisfies the boundary conditions is obtained using the principle of minimum potential energy. The results obtained by ANSYS software have been used to corroborate the correctness of the analytical model. In addition, effects of various structural parameters (such as ply angles and skin-to-core thickness ratio) on buckling behavior of ECCSS have been investigated.